When Technology Enters at Home: The Challenges of Home Health Care Providers in a Developing Country. Issue 4 (October 2021) - Asgari, Parvaneh; Dehghan Nayeri, Nahid; Bahramnezhad, Fatemeh; Fattah Ghazi, Samrand; Esmaeili, Maryam
Abstract : The number of patients with chronic diseases requiring invasive mechanical ventilation at home is increasing. Thus, identifying the challenges of this valuable type of care can be an elective step for achieving health-related goals. This study was conducted to determine the challenges faced by home health care providers. Three themes emerged from the data analysis: (1) hospital-based challenges with 2 subthemes: the family unpreparedness for home care and the lack of continuous education; (2) home health care agency challenges with 2 subthemes: home health care workers and the deficiency in organizational policies; and (3) economic challenges. Three themes of hospital-related challenges, home health care agency challenges, and economic challenges that emerged in the study showed that support from the insurance system, improvement of home care agency policies, and holistic care for patients through a multidisciplinary team approach are essential for addressing the current challenges of care for patients under invasive mechanical ventilation at home.